Homicide Data, Third Revision - Fearon, James D. (World Bank, Washington, DC, 2017)
This brief paper summarizes results from an analysis of the World Development Report (WDR) homicide dataset (February 24, 2010), which is based primarily on estimates from the United Nations Office against Drugs and Crime (UNODC), with some changes or additions from national sources and the World Health organization (WHO). Although homicide rates appear to be the most reliable cross-national measure of crime, the best estimates have are still probably much less reliable than parallel measures have for presence and scale of civil conflict involving organized armed groups. This is so for two main reasons. First, the data are collected and reported by country agencies (police, usually), and procedures, definitions, and competence can vary greatly across countries and over time within them. Looking at the time series for particular countries suggests in many cases that large changes must be due to changed procedures or data collection policies, rather than changes in actual homicide rates. Second, there is a great deal of missing data.